2017
DOI: 10.4103/1735-3327.201132
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral health-related quality of life in 9-15 year old children with visual impairment in Uttarakhand, India

Abstract: Background:To assess the prevalence of dental diseases among 9–15-year-old visually impaired children and find out its impact on their daily activities using the Child-Oral Impact on Daily Performance (C-OIDP) questionnaire in districts of Uttarakhand, India.Materials and Methods:A total of 423 visually impaired institutionalized children between the age group of 9–15 years were included in the study. Stratified random sampling technique was used to obtain the study population. Dental caries was recorded using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 20 publications
7
28
1
4
Order By: Relevance
“…These children have been found to have poor oral health‐related quality of life as assessed by the Child‐Oral Impact on Daily Performance (C‐OIDP) questionnaire converted in Braille. This study also recommended the implementation of ‘tailor‐made special oral health care measures’ at the earliest in these children. Lack of a ‘customised awareness programme’ for visually impaired children has also been cited as the probable reason for increased mean oral hygiene index scores and number of bleeding sites in visually impaired children compared with sighted counterparts, despite having more consistent brushing habits due to the institutional settings.…”
Section: Discussionmentioning
confidence: 96%
“…These children have been found to have poor oral health‐related quality of life as assessed by the Child‐Oral Impact on Daily Performance (C‐OIDP) questionnaire converted in Braille. This study also recommended the implementation of ‘tailor‐made special oral health care measures’ at the earliest in these children. Lack of a ‘customised awareness programme’ for visually impaired children has also been cited as the probable reason for increased mean oral hygiene index scores and number of bleeding sites in visually impaired children compared with sighted counterparts, despite having more consistent brushing habits due to the institutional settings.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, in cases of impaired vision, a high prevalence of caries (due to poor oral hygiene) and dental traumatic injuries in permanent and primary dentition have been observed, leading to a reduction of scores in oral health-related quality of life (OHRQoL). 19,20 Cunha et al also concluded that patients with an acquired impaired vision presented a worse periodontal status compared with patients with congenital impaired vision, regardless the severity of the impairment. 21 As regards, the patient's nutritional habits, including the excessive consumption of beverages, the correlation between the impaired vision and the taste sensitivity and nutritional preferences is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in cases of impaired vision, a high prevalence of caries (due to poor oral hygiene) and dental traumatic injuries in permanent and primary dentition have been observed, leading to a reduction of scores in oral health‐related quality of life (OHRQoL) . Cunha et al.…”
Section: Discussionmentioning
confidence: 99%
“…The Sudanese study had wider age range but fewer participants than the present study. An Indian study on assessment of oral health‐related quality of life among 9‐ to 15‐year‐old visually impaired children using the Child‐OIDP questionnaire reported an overall severity of impact of 30.45%, which was mainly due to dental caries and maximum impact on sleeping, studying and eating …”
Section: Discussionmentioning
confidence: 99%